(untitled) (Journal of the Bangladesh Agricultural University, 2025)
An experiment was conducted at the Horticulture Farm and Postgraduate Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during November 2023 to February 2024, to evaluate the effects of variety and organic mulching on the growth, yield, and quality of carrots. The two-factor experiment was laid out in a two-factor Randomized Complete Block Design with three replications. The factor A comprised of three carrot varieties viz. V1 = Kuroda Improved (Tokita), V2 = New Kuroda, and V3 = Improved Shin Kuroda, and Factor B comprised of four organic mulching treatments viz., M0 = No mulching (control), M1 = Rice straw, M2 = Water hyacinth, and M3 = Sawdust. Results revealed significant variations in all the parameters studied. Among the varieties, New Kuroda showed superior performance, producing the highest plant height (63.50 cm), number of leaves (8.77) at 70 DAS, maximum root length (16.40 cm), root diameter (3.30 cm), individual root weight (116.95 g), marketable yield (41.80 t/ha), minimum weight loss (37.01%), higher TSS (17.65 %brix) and shelf life (10.90 days). Among the mulching treatments, rice straw mulch produced maximum plant height (64.28 cm) at 70 DAS, root length (15.70 cm), root diameter (3.23 cm), individual root weight (116.15 g), and marketable yield (41.57 t/ha), minimum weight loss (36.68%), highest TSS (18.87 %brix) and shelf life (10.61 days). Combined effects between variety and mulching were also statistically significant at all stages. The combination of New Kuroda with rice straw mulch performed the best across most traits, producing the tallest plants (65.93 cm), longest roots (17.56 cm), widest root diameter (3.57 cm), the highest individual root weight (965.17 g), and the greatest marketable yield (29.41 t/ha), while the lowest values were recorded from the control treatment. These results suggest that the combined effect of a suitable variety and mulching practice has a synergistic impact on carrot production. Therefore, it can be concluded that the New Kuroda variety with straw mulch was found to be better in respect of growth, yield, and quality of carrot compared to other treatments. J Bangladesh Agril Univ 23(4): 468–483, 2025